2010
DOI: 10.1136/bmj.b5444
|View full text |Cite
|
Sign up to set email alerts
|

The effects of baseline characteristics, glycaemia treatment approach, and glycated haemoglobin concentration on the risk of severe hypoglycaemia: post hoc epidemiological analysis of the ACCORD study

Abstract: Objectives To investigate potential determinants of severe hypoglycaemia, including baseline characteristics, in the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial and the association of severe hypoglycaemia with levels of glycated haemoglobin (haemoglobin A1C) achieved during therapy.Design Post hoc epidemiological analysis of a double 2×2 factorial, randomised, controlled trial.Setting Diabetes clinics, research clinics, and primary care clinics.Participants 10 209 of the 10 251 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
311
10
12

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 385 publications
(364 citation statements)
references
References 23 publications
31
311
10
12
Order By: Relevance
“…In contrast, the independent determinants of severe hypoglycemia were older age, limited education, hypertension, renal insufficiency, and mild cognitive impairment. These observations are also consistent with those of other reports (5,(13)(14)(15)(16)(17). Stated in clinically relevant terms, these analyses suggest that an individual with a BMI of 25 kg/m 2 would be ;30% more likely to have nonsevere hypoglycemia than one with a BMI of 35 kg/m 2 , but with no difference in the risk of severe hypoglycemia.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, the independent determinants of severe hypoglycemia were older age, limited education, hypertension, renal insufficiency, and mild cognitive impairment. These observations are also consistent with those of other reports (5,(13)(14)(15)(16)(17). Stated in clinically relevant terms, these analyses suggest that an individual with a BMI of 25 kg/m 2 would be ;30% more likely to have nonsevere hypoglycemia than one with a BMI of 35 kg/m 2 , but with no difference in the risk of severe hypoglycemia.…”
Section: Discussionsupporting
confidence: 91%
“…9 An unexpected finding was that patients with dementia showed significantly higher A1c levels compared with those who did not experience severe hypoglycemia. Indeed, the literature has shown that lower A1c levels are generally associated with severe hypoglycemia 22,23 ; however, specific information on A1c levels in patients with dementia experiencing severe hypoglycemia are scare. A previous report in a large longitudinal study of older patients with type 2 diabetes also found significantly higher A1c levels in those who had experienced a severe hypoglycemic event compared with those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…However, an epidemiological analysis of the ACCORD trial suggests that the risk of hypoglycaemia resulting in emergency medical care or admission to hospital is progressively higher in type 2 diabetes participants with lower baseline HbA1c when comparing intensive vs standard glucose-lowering treatments (around 2-times for values ≥8.5%; 3-times for values between 7.5-8.4%; and 7-times for values <7.5%). 33 It is noteworthy that the individualised identification of HbA1c targets is just one of a number of approaches to the problem of hypoglycaemia. 10 In observational studies, structured diabetes education reduce the burden of hypoglycaemia; 10 yet, attendance at structured education programs remains very low (5.3%) and further effort should be put in place to identify and address local barriers.…”
Section: Implications For Clinicians and Policymakersmentioning
confidence: 99%